DNA barcoding: bioinformatics and phylogenetic workflow in R - Kanthaswamy, Sree; Wilson, John-James; Malaivijitnond, Suchinda (Elsevier, 2025)
DNA barcoding is used to (i) assign taxonomic identity to unknown organisms and (ii) obtain taxonomic information about cryptic species. It involves sequencing a fragment of mitochondrial COI gene (=DNA barcodes) from specimens and performing comparisons with a library of DNA barcodes of known taxonomy. Here, in an update to the previous edition, we provided step-by-step instructions for using R, an open-source offline platform, to (1) convert sequencing reads into DNA barcodes and (2) analyse the barcodes with phylogenetic trees. We also provided steps of using BOLD, an online COI database, to perform the assignment of taxonomic identity.